Docetaxel, cisplatin and 5-FU compared with docetaxel, cisplatin and cetuximab as induction chemotherapy in advanced squamous cell carcinoma of the head and neck: Results of a randomised phase II AGMT trial. (July 2021) - Keil, Felix; Hartl, Maximilian; Altorjai, Gabriela; Berghold, Andrea; Riedl, Regina; Pecherstorfer, Martin; Mayrbäurl, Beate; De Vries, Alexander; Schuster, Judith; Hackl, Jutta; Füreder, Thorsten; Melchardt, Thomas; et al.
Abstract: Purpose: Induction chemotherapy (ICT) with cisplatin (P), 5-FU (F) and taxanes (T) is a therapeutical option in patients suffering from locally advanced or unresectable stage III or IV squamous cell carcinoma of the head and neck (SCCHN). The role of ICT is controversial, and toxicity and/or delay of radiotherapy (RT) may reduce the potential benefit of this treatment regimen. Here, we report the results of a randomised phase II trial comparing TPF with TP + cetuximab (C). Patients and methods: In this trial, 100 patients with locally advanced stage III or IV SCCHN were included in the analysis. Patients were randomly assigned to either TPF-ICT (N = 49) or TPC-ICT (N = 51), both followed by RT + C. The primary end-point of the study was overall response rate (ORR) three months after RT + C was finished. Results: On an intention-to-treat basis, the ORR (complete remission + partial remission) was 74.5% in the TPC arm compared with 63.3% in the TPF arm ( p = 0.109). OS was similar in both arms 400 days after treatment was initiated (86.1% [95% confidence interval CI, 73.0–93.1%] in the TPC arm and 78.5% [95% CI, 63.7–87.8%] in the TPF arm). TPC resulted in slightly less serious adverse events and in less haematological, but more skin toxicities. Two patients randomised in the TPC arm died during ICT and RT. Four patients in the TPF arm died after completion of RT. No delay from the end of ICT to RT + C was observed. A total of 83.1% of patients (80% in the TPC arm; 86% in the TPF arm) received RT without dose reduction and/or modification. Conclusion: TPC-containing ICT for patients with locally advanced SCCHN was found to be an effective and tolerable one-day regimen. Further prospective evidence from larger trials is warranted. Highlights: Phase II randomised trial comparing two induction chemotherapy (ICT) regimens. Substitution of 5-FU with cetuximab in docetaxel- and cisplatin-containing ICT. Both regimens result in similar response rates. Cetuximab-containing ICT is a less laborious one-day treatment option. Results in decreased haematological, but increased cutaneous toxicity.